Sjögren: unique surname, two men, four syndromes and one disease - Rodrigues, José Vitor Alécio; Lima, Fábio Antônio Serra de, Júnior; Barros, Daniel Pereira Maurício de; Franklin, Gustavo Leite; Nepomuceno, Adriana Meira Tiburtino; Braz, Alessandra de Sousa; Teive, Hélio A. G.; Meira, Alex T. (Arquivos de Neuro-Psiquiatria, 2024)
Henrik and Torsten Sjögren (/ˈʃoʊɡrən/ or SHOH–grən) were two Swedish physicians living in the same period, but completely unrelated, except for their notable contributions to Medicine. The first one described keratoconjunctivitis sicca, afterward called Sjögren's syndrome, and a fishing net aspect retinal pigmentation affecting visual acuity, nowadays known as Sjögren reticular dystrophy. The last one contributed to the understanding of Spielmeyer-Sjögren disease, Marinesco-Sjögren, and Sjögren-Larsson syndromes, all related to genetic disorders and neurological symptoms. In this paper, we aim to describe each disorder, in order to avoid any misunderstanding in diagnosis and for historical record.
Keywords: Sjogren's Syndrome; Retinal Pigment Epithelium; Sjogren-Larsson Syndrome; Neuronal Ceroid-Lipofuscinoses; Spinocerebellar Degenerations